2021- IFAD-UE/CCAFS CSA Monitoring: Cinzana Climate-Smart Village (Mali) - Bonilla-Findji, Osana; Eitzinger, Anton; Ouedraogo, Mathieu; Zougmoré, Robert B.; Läderach, Peter R.D.; Dembélé, Siaka (2021)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Cinzana Climate Smart Village (Mali) in February 2021. This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: adoption of CSA practices and technologies, as well as access to climate information services and their related impacts at household level and farm level